Chapter 12 Modelling Threshold-Dependent Gene Drives: a Case Study Using Engineered Underdominance - Edgington, Matthew P. (CABI, 2022)
In this chapter, we outline a range of modelling approaches that have been used to demonstrate the key characteristics of this approach, including threshold introduction frequencies, reversibility, spatial limitation and robustness to mutation/resistance. We then go on to discuss alternative configurations based on the use of sex-specific components and their effect on introduction thresholds. We conclude with a discussion on the cycle of information between mathematical models and experimental data along with a range of areas for future modelling that will be important in providing information on the anticipated effects of these systems when released into target populations.